An experimental investigation on the progressive failure of an additively manufactured Laser Powder Bed Fusion Ti-6Al-4V aero-engine bracket under Low Cycle Fatigue. (September 2022) - Gupta, Alok; Bennett, Chris J.; Sun, Wei
Highlights: Cyclic loading with higher plasticity levels increases the dislocation density and contributes towards cyclic softening. The SLM bracket in strut & connector design met its LCF cycle target under operational normal loading. Failures in the bracket were observed under the extreme LCF loading condition. Failure of the bracket was progressive in nature and occurred at discrete LCF cycles. SLM Ti-6Al-4V bracket is found to have good redundancy in its load transfer path. Abstract: The Low Cycle Fatigue (LCF) performance of an aero-engine bracket in a 'struts and connectors' design, made using the Laser Powder Bed Fusion (LPBF) process has been studied using strain controlled LCF tests at different Strain Ranges (SR). From the cyclic test results, the bracket has demonstrated that it meets the target LCF performance which was in excess of the normal expected operating loads that the LPBF bracket would experience. The failures in the bracket at different locations were observed only under the extreme loading conditions. The failure of the bracket was of a progressive nature with failure of different struts/connectors happening at different discrete cycles. Even after the first five failures, the LPBF bracket had 47% of the original load carrying capacity in the tensile part of the hysteresis loop, indicating a good redundancy in its load transfer paths. In general, the surface locations of the bracket struts/connectors, where there are lack of fusion voids, were the prime sites for crack initiation. If any of these locations also coincide with high stresses, i.e. the combination of 'size of defect' and 'magnitude of stress', then this will contribute to an increased likelihood of failure at these locations in the LPBF bracket.